A randomized comparative study between intralesional vitamin D3 and intralesional triamcinolone acetonide in the treatment of alopecia areata - Marwa E. Eldeeb; Muhammad M.F. Abdelmoula; Khaled F. El Mulla (Journal of the Egyptian Women’s Dermatologic Society)
Background Alopecia areata (AA) is a common hair loss disorder. Despite the availability of various treatment options, no single agent consistently cures this condition. Vitamin D, with its immunomodulatory effects, emerges as a promising treatment avenue for AA. Objective To assess the safety and efficacy of intralesional vitamin D3 compared with intralesional triamcinolone acetonide (TAC) in AA. Also, the treatment response should be analyzed according to serum vitamin D3 levels. Patients and methods This randomized controlled trial involved 40 patients aged 12 years and older with patchy active AA involving less than 50% of the scalp. The patients were randomized into two groups: group A received intralesional TAC, and group B received intralesional vitamin D3. Each patient underwent four treatment sessions and two follow-up sessions at monthly intervals. Serum vitamin D3 levels were assessed at the baseline. The regrowth score (RGS) was used to assess clinical improvement. Results Both groups showed significant improvement in mean RGS at the 16th and 20th weeks compared with the fourth week (P<0.001; for both groups at the 16th and 20th weeks). By the 20th week, the mean RGS reached 3.05 in group A and 2.55 in group B (P=0.398). No significant difference was found between good and poor responders regarding vitamin D levels. Trichoscopic signs of activity improved significantly in both groups, and both treatment modalities were safe, with minor side effects. Conclusion Intralesional vitamin D is comparable in efficacy and safety to intralesional TAC in patchy AA of the scalp. Also, the response to treatment was insignificantly influenced by the level of serum vitamin D.